Performance Appraisal Methods That Are Effective in The Covid-19 Pandemic Using Systematic Literature Review - Christian Wiradendi WOLOR; Agung Wahyu HANDARU; Ahmad NURKHIN; Yudin CITRIADIN (Communications of International Proceedings, 2021)
In the context of performance management in an organization, it is important to continue to assess the performance of each employee even though during the Covid-19 pandemic, it was difficult to make an assessment directly and was carried out with the help of internet technology media. The performance appraisal system becomes the basis for the organization for the development of human resources and systems that can provide avenues for making important decisions for the organization. The purpose of this study is to present recommendations for employee performance appraisal approaches during the Covid-19 pandemic. This research is a Systematic Literature Review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analysis) method which is carried out systematically by following the correct stages or research protocols. The results of this study recommend that the MBO approach and 720 degrees can be used as a reference in assessing employee performance during a pandemic like this. Where employee performance is determined from the results measured by involving negotiations between managers and employees and also external communication relations can be used as a tool for innovation and organizational improvement.
Keywords: Performance; Performance Appraisal Method; Covid-19.